Evaluation of Salivary Glucose, IgA and Flow Rate in Diabetic Patients: A Case-Control Study - P. Bakianian Vaziri; M. Vahedi; H. Mortazavi; Sh. Abdollahzadeh; M. Hajilooi (Tehran University of Medical Sciences, 2010)
Objective: An association between diabetes mellitus and alterations in the oral cavity has been noted. In this study, we evaluated differences between salivary IgA, glucose and flow rate in diabetic patients compared with healthy controls. Materials and Methods: Forty patients with type 1 diabetes, 40 patients with type 2 diabetes and 40 healthy controls were selected. Whole unstimulated saliva samples were collected by the standard method and the salivary flow rate was determined. Nephelometric and Pars method were used to measure salivary IgA and salivary glucose concentrations, respectively. Statistical analysis was performed by Chi-square and t test. Results: There were no significant differences in salivary IgA and glucose concentrations between type 1 and type 2 diabetic patients and their matched control subjects (P>0.05). Salivary flow rate was significantly lower in diabetic patients (P<0.05). In addition, DMFT was higher in diabetic patients than the controls. Conclusion: Determination of salivary constituents may be useful in the description and management of oral findings in diabetic patients.